1997
DOI: 10.1021/cm970208s
|View full text |Cite
|
Sign up to set email alerts
|

Heat Treatment of Alumina Aerogels

Abstract: The phase conversions and morphological changes of alumina aerogel films and monoliths during heat treatment were investigated by TGA/DTA, BET, XRD, and image analysis of SEM micrographs. A preliminary model explaining the structural evolution of the film during heat treatment is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
33
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 19 publications
6
33
0
1
Order By: Relevance
“…A mature and common method is classical sol-gel process which uses metal alkoxides as precursors. This method has been applied successfully to prepare several kinds of aerogels [1,[11][12][13], such as SiO 2 , Al 2 O 3 and TiO 2 . But it is not very suitable for preparing many other kinds of metal oxide aerogels, just like ZrO 2 , Nb 2 O 5 and RuO 2 [14,15], because many metal alkoxides (the precursor of those aerogels) are rare or difficult to synthesize.…”
Section: Introductionmentioning
confidence: 99%
“…A mature and common method is classical sol-gel process which uses metal alkoxides as precursors. This method has been applied successfully to prepare several kinds of aerogels [1,[11][12][13], such as SiO 2 , Al 2 O 3 and TiO 2 . But it is not very suitable for preparing many other kinds of metal oxide aerogels, just like ZrO 2 , Nb 2 O 5 and RuO 2 [14,15], because many metal alkoxides (the precursor of those aerogels) are rare or difficult to synthesize.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminas are commonly obtained from four precursors: two hydroxides, gibbsite (11) and bayerite (12); and two oxyhydroxides, diaspore (13) and boehmite. Although this last phase has been widely used for preparing aluminas, a detailed characterization of boehmite is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Clear crystal phases were not detected and it was suggested that the coating film consisted of amorphous phase. Yamaguchi et al reported that alkoxide-derived boehmite gel heat-treated at 803 K showed an amorphous phase and changed to £-Al 2 O 3 at 1008 K. 23) On the other hand, Keysar et al investigated the heat-treatment change of alkoxide-derived boehmite aerogel and concluded that the aerogel heat-treated at 873 K showed ©-Al 2 O 3 and changed to ª-Al 2 O 3 at 1473 K. 24) It is possible that the presence of SiO 2 prevented the crystallization of Al 2 O 3 in our experiment.…”
Section: Preventing the Formation Of Cr(vi)mentioning
confidence: 99%